Coronavirus y wigka küxan: la percepción mapuche de la pandemia - Jesús Antona Bustos (Nuevo mundo - Mundos Nuevos, 2021)
The tendency to impose measures designed from rich contexts to contain this type of pandemics ignores that a large part of the vulnerability of Amerindian peoples derives from the precarious economic, social and political conditions they have at their disposal to resolve them autonomously. This work focuses on the case of the Mapuche people of Chile and how they perceive the global pandemic from their local contexts, taking as a source their discursive production on the Internet, which is characterized by its immediacy and for being conceived for action. I will focus especially on some cultural and political representations of the coronavirus and on the socio-cultural relevance of the measures adopted for its prevention in the first months of the pandemic. From the different histories and communications it is clear that the past and the present overlap and that the disease is conceived within a continuum of dispossession and violence; hence the concept that best allows this pandemic to be framed within Mapuche culture is that of wigka küxan: the disease of colonialism and dependency.